A 24-bp Indel (Insertion-Deletion) Polymorphism in Promoter Prolactin Gene - Lumatauw, Sintje; Mu’in, Muh Affan (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2016)
Prolactin in chicken (cPRL) is a polypeptide hormone that plays a crucial role in incubation and brooding behavior. This hormone is coded by a gene that located at chromosome 2. The objective of this study was to investigate 24-bp indel polymorphism in promoter prolactin gene of Papua local chickens. A number of 60 DNA samples came from 60 Papua local chickens (25 males and 35 females) were used in this study.Â PCR (Polymerase Chain Reaction) method with a pair of specific primer was applied and a specific DNA fragment with 130 and/or 154 bp contained 24-bp indel was successfully amplified. Results of electrophoresis run on 1.5 % agarose gel showed three genotypes: II, ID and DD with the frequency of 6,7%, 48.3% and 45% respectively. The frequency of I allele was 0.31 and D allele was 0.69. Results indicated Â that the I allele frequency was medium in Papua local chickens population. Results therefore suggest that incubation behavior in hen population of Papua local chickens is easy to eliminate by increasing the I allele frequency in the population.